THE POTENTIAL OF NANOTECHNOLOGY IN DENTISTRY - Alzaagi, Ahmed Abdulaziz A, Hala Hadab Alenazi, Talal Hazeem Alshmmari, Saad Hamed Alshammari, Munif Zahi Alenazi, Fahad Fadel Alshammari, ‏Maram Fayez M Alshammari, Saleh Mohammed Alzughaibi (Chelonian Research Foundation, 2022)
The physical, chemical, and biological characteristics of structures and their constituent parts at the nanoscale are the focus of nanotechnology. The idea behind nanotechnology is to regulate individual atoms and molecules to create functioning structures. Numerous advancements in the fields of materials science, biotechnology, electronics and computer technology, aviation, space exploration, and health sciences will be made possible by the application of this technology. Nanotechnology is particularly expected to deliver breakthroughs in dentistry and novel approaches to oral health-related diagnostic and therapeutic procedures, in tandem with improvements in materials science and biotechnology. (2013) Eur J Dent 7:145–151 Key words: nanocomposite, nanotechnology, dentistry, and Nano dentistry.